2011
DOI: 10.3892/ol.2011.449
|View full text |Cite
|
Sign up to set email alerts
|

High-dose toremifene as first-line treatment of metastatic breast cancer resistant to adjuvant aromatase inhibitor: A multicenter phase II study

Abstract: Abstract. There is currently no standardized therapy available for metastatic breast cancer in patients with aromatase inhibitor (AI)-resistant breast cancer. We conducted a prospective study to examine the efficacy and safety of high-dose toremifene (TOR) treatment for the first-line treatment of metastatic breast cancer following AI adjuvant therapy. A multicenter phase II study was designed (Registry no.: UMIN000000489). Inclusion criteria comprised hormone-responsive postmenopausal women who had received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…More recent data with toremifene should stimulate further research. Outstanding issues include: i) reasonably convincing phase III data and a meta-analysis suggesting similar efficacy and safety for adjuvant toremifene compared with tamoxifen in postmenopausal HR þ breast cancer 34,[36][37][38]63 ; ii) suggestions from a comparative trial that toremifene and letrozole showed similar efficacy as first-line therapy for postmenopausal patients with hormone receptor-positive metastatic breast cancer 39 ; iii) conflicting data in the ATAC trial, which showed potential antagonism between anastrozole and tamoxifen in combination vs. anastrozole alone, while the combination of toremifene and a different aromatase inhibitor, atamestane, showed results equivalent to those of letrozole 40 ; iv) suggestions that higher than standard doses of toremifene might be effective in patients for whom aromatase inhibitors have failed or even in patients progressing on tamoxifen [42][43][44]46 ; v) a controversial study from China suggesting that toremifene use in premenopausal patients in the adjuvant setting (in the absence of meaningful clinical trial data in premenopausal women) was not inferior to tamoxifen use. 51 Finally, despite clinical controversies surrounding alterations in CTP2D6 on tamoxifen outcomes, it is clear that the toremifene mechanism of action is independent of CYP2D6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent data with toremifene should stimulate further research. Outstanding issues include: i) reasonably convincing phase III data and a meta-analysis suggesting similar efficacy and safety for adjuvant toremifene compared with tamoxifen in postmenopausal HR þ breast cancer 34,[36][37][38]63 ; ii) suggestions from a comparative trial that toremifene and letrozole showed similar efficacy as first-line therapy for postmenopausal patients with hormone receptor-positive metastatic breast cancer 39 ; iii) conflicting data in the ATAC trial, which showed potential antagonism between anastrozole and tamoxifen in combination vs. anastrozole alone, while the combination of toremifene and a different aromatase inhibitor, atamestane, showed results equivalent to those of letrozole 40 ; iv) suggestions that higher than standard doses of toremifene might be effective in patients for whom aromatase inhibitors have failed or even in patients progressing on tamoxifen [42][43][44]46 ; v) a controversial study from China suggesting that toremifene use in premenopausal patients in the adjuvant setting (in the absence of meaningful clinical trial data in premenopausal women) was not inferior to tamoxifen use. 51 Finally, despite clinical controversies surrounding alterations in CTP2D6 on tamoxifen outcomes, it is clear that the toremifene mechanism of action is independent of CYP2D6.…”
Section: Discussionmentioning
confidence: 99%
“…A second, prospective, multicenter study examined toremifene 120 mg daily in hormone-responsive postmenopausal women who had received adjuvant AI therapy postoperatively for > 1 year and had relapsed during the treatment or within 12 months of completion of adjuvant therapy. 43 Because of the difficulty with accrual, only 13 patients were enrolled in this study; however, the authors report 1 patient with partial response (7.7%) and 5 patients (38.5%) with stable disease > 6 months, for a clinical benefit rate of 46.2% with toremifene 120 mg. 43 In addition, Yamamoto et al retrospectively evaluated the effect of toremifene 120 mg day for the treatment of breast cancer in 83 women who relapsed on AIs. 44 Of these 83 patients, 12 patients (15%) achieved partial response and 24 patients (30%) had stable disease for 24 weeks, demonstrating clinical benefit in 45% of patients.…”
Section: Toremifene Vs Aromatase Inhibitors and After Aromatase-inhimentioning
confidence: 99%
“…There are currently 2 main chemical classes of SERMs approved for clinical use: the first-generation triphenylethylene derivatives, tamoxifen [110] and toremifene [111, 112], which are used in the treatment and in the case of tamoxifen in the prevention of breast cancer [65, 113]; and raloxifene, a second-generation benzothiopene derivative indicated for the treatment and prevention of osteoporosis [29] and the reduction of breast cancer incidence in high risk post-menopausal women [31]. All 3 compounds also have beneficial effects on serum lipids, but are still associated with adverse effects such as hot flushes and an increase in the risk of venous thromboembolism (VTE).…”
Section: The Current and Next Generation Of Sermsmentioning
confidence: 99%
“…In 1979, Craig was to be 110 the opening speaker at the tamoxifen meeting in Sorrento, Italy. He was working in 111 Bern, Switzerland, and was scheduled to fly down on an Alitalia flight from Zurich 112 to Naples on the evening before his talk. Craig had to leave Zurich on the last flight 113 that evening, as he had a site visit at the Institute in Bern AU2 earlier in the day.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…There are currently 2 main chemical classes of SERMs approved for clinical use: the first-generation triphenylethylene derivatives, tamoxifen [110] and toremifene [111,112], which are used in the treatment and in the case of tamoxifen in the prevention of breast cancer [65,113]; and raloxifene, a second-generation benzothiopene derivative indicated for the treatment and prevention of osteoporosis [29] and the reduction of breast cancer incidence in high risk postmenopausal women [31]. All 3 compounds also have beneficial effects on serum lipids, but are still associated with adverse effects such as hot flushes and an increase in the risk of venous thromboembolism (VTE).…”
Section: The Current and Next Generation Of Serms Tamoxifen And Raloxmentioning
confidence: 99%